2013
DOI: 10.1016/j.neures.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling regulates nucleocytoplasmic Olig2 translocation in reactive astrocytes differentiation after ischemic stroke

Abstract: Treatment with DAPT, an inhibitor of the Notch-activating enzyme, γ-secretase is known to reduce damage to ischemic brain. However, the molecular mechanisms supporting this therapeutic effect are not fully understood. Here we demonstrated that Notch/RBP-J signaling is activated in NG2(+) glial progenitors and reactive astrocytes such as GFAP(+) cells, Nestin(+) cells and RC2(+) cells, using Notch/RBP-J signaling reporter mice. 3-day DAPT treatment reduced the number of reactive astrocytes but not NG2(+) glial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The microglia-mediated inflammatory response associated with focal ischemic stroke can be attenuated by γ-secretase inhibition to reduce the number of activated microglia and the expression of pro-inflammatory cytokines such as IL-1β and TNF . In addition, a recent study has shown that γ-secretase inhibition reduces the proliferation and differentiation of reactive astrocytes following stroke, in association with reduced ischemic brain injury (Marumo et al, 2013).…”
Section: Stroke and Alzheimer's Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…The microglia-mediated inflammatory response associated with focal ischemic stroke can be attenuated by γ-secretase inhibition to reduce the number of activated microglia and the expression of pro-inflammatory cytokines such as IL-1β and TNF . In addition, a recent study has shown that γ-secretase inhibition reduces the proliferation and differentiation of reactive astrocytes following stroke, in association with reduced ischemic brain injury (Marumo et al, 2013).…”
Section: Stroke and Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…γ-Secretase substrate γ-Secretase cleavage product Effects in inflammatory disease References Notch NICD ALPS and SLE increase lymphoproliferation, DNT, autoantibody production, and nephritis Teachey et al, 2008 Rheumatoid arthritis mediates TNF-α-induced IL-6 production; exacerbates RA symptoms; increases ICAM-1, NF-κB, proinflammatory cytokines, Th1 and Th17 cells, Th17 cell differentiation Jiao et al, 2012Park et al, 2013Jiao et al, 2014 Multiple sclerosis induces Th1 polarization by up-regulating Tbx21; regulates Th17 differentiation; increases Th17-associated cytokine secretion; cytosol localized NICD causes remyelination failure in OPCs in MS lesion Minter et al, 2005Keerthivasan et al, 2011Nakahara et al, 2009 Sepsis mediates the production of LPS-induced cytokines Tsao et al, 2011 Asthma increases Th2 cytokine levels by up-regulating GATA-3; decreases Th1 cytokine levels Kang et al, 2009 Systemic sclerosis exacerbates dermal fibrosis; increases profibrotic cytokines Dees et al, 2011 Behcet's disease increases Th17 response Qi et al, 2014 Ulcerative colitis enhances IL-22 induced STAT3 dependent transcription Murano et al, 2014 Ischemic stroke activates microglia cells; enhances leukocytes infiltration; promotes proliferation and differentiation of reactive astrocytes Arumugam et al, 2006Wei et al, 2011Park et al, 2013Cheng et al, 2014Marumo et al, 2013Shimada et al, 2011 Allergic airway inflammation induces IL-4 production, Th2 differentiation, airway hyperresponsiveness, and eosinophilic airway inflammation Okamoto et al, 2009 Atherosclerosis increases macrophage accumulation and activity in atherosclerotic lesion; attenuates the progression of atherosclerosis Aoyama et al, 2009 Calcific aortic stenosis enhances inflammatory response to TLR4 stimulation in human aortic valve interstitial cells through regulating NF-κB activation Zeng et al, 2012 Other inflammatory responses peripheral T cell activation and proliferation (canonical & noncanonical notch signaling); induces M1 polarization of LPS-stimulated macrophage and microglial cells; inhibits eosinophil differentiation Palaga et al, 2003Dongre et al, 2014Wang et al, 2010Liu et al, 2012Kang et ...…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Mature astrocytes are quiescent and do not divide in a healthy brain; however, they acquire a proliferative phenotype following cerebral injury (Barreto et al, 2011; Li et al, 2014). In an ischemic stroke, It was reported that Notch 1 signaling was activated in astrocytes in the peri-infarct region by 24 h (Marumo et al, 2013) and tamoxifen induced deletion of Notch 1 from GFAP positive cells resulted in a decreased number of proliferating astrocytes following injury. The study also suggested that Notch 1 signaling in reactive astrocytes may aid in suppression of immune response into the peri-infarct area as Notch 1 knockout animals had significantly higher invading immune cells (Shimada et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The study also suggested that Notch 1 signaling in reactive astrocytes may aid in suppression of immune response into the peri-infarct area as Notch 1 knockout animals had significantly higher invading immune cells (Shimada et al, 2011a). Some speculation existed among researchers concerning the source of Notch 1 in the peri-infarct area, as some scientists believed that NG2+ cells also expressed a Notch 1 positive stain along with reactive astrocytes, but genetic fate mapping analysis revealed that a subpopulation of reactive astrocytes—not NG2+ cells—activated Notch1 signaling in response to injury and became proliferative (Komitova et al, 2011; Marumo et al, 2013). In addition, it was suggested that activation of Notch 1 signaling in reactive astrocyte after stroke may redirect the cells to dedifferentiate into astrocytes derived neural stem cells (Shimada et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The levels of both γ-secretase and NICD are elevated in primary neurons as well as in ipsilateral tissue following ischemia (Li et al, 2012; Arumugam et al, 2010). Besides enhancing apoptotic cascades in neurons, Notch may have an important role in microglial activation and lymphocyte infiltration in stroke (Wei et al, 2011; Marumo et al, 2013). Moreover, an apoptotic role for Notch2 was also documented in ischemic stroke (Alberi et al, 2010).…”
Section: Notch In Ischemic Strokementioning
confidence: 99%